The Phenomenon of Stunting on the Academic Results of Elementary School Students (Universitas Pendidikan Indonesia Kampus Cibiru, 2025)
Every human being born on this earth will experience a process in their life. This process includes development and growth starting from birth to death. Therefore, it is important to have adequate nutritional intake to support children's growth, so that stunting does not occur. The aim of our article is to find out how influential stunting and several other factors are on cognitive development in children. The method used in this writing is a literature review using a comprehensive strategy via the internet, such as searching for articles or national journals. In the final stage, a total of thirteen journals were collected, including ten bibliography journals and three of them were literature journals, which in the end of the thirteen journals were summarized into one journal which studied